(untitled) (Masjiduna : Junal Ilmiah Stidki Ar-Rahmah, 2024)
The Taqwa Mosque in Pecing, Sragen, illuminates efforts towards optimizing the mosque’s role through the "Kampung Sedekah" program, engaging the community in fundraising activities to augment the mosque’s financial resources for operational expenses related to mosque programs. The inception of the "Kampung Sedekah" program stems from a meager income, insufficient to meet the operational needs of the mosque. Recognizing this, the mosque’s Takmir encourages the Pecing community to actively participate in this philanthropic initiative, whereby the proceeds directly benefit the community through the mosque. This research investigates community involvement in fundraising for the Taqwa Mosque’s "Kampung Sedekah" program in Pecing, Sragen. Employing a qualitative methodology with a case study approach, the research unfolds at the Taqwa Mosque in Pecing, Sragen, utilizing data collection techniques such as observation, interviews, and documentation. The findings indicate that community engagement in the "Kampung Sedekah" program brings about positive transformations for both the mosque and the community. The mosque’s financial inflow stabilizes, its programs diversify, and the congregation participating in obligatory prayers witnesses an increase. The success of the program hinges on wholehearted support from the Pecing community; without such backing, the program’s success would remain elusive. This research aims to inspire other mosques, particularly those in rural areas, in enhancing their financial resources through community-based fundraising initiatives.